دور المنظمة الدولية للعمل في حماية حقوق العمال المهاجرين وأفراد أسرهم - علي، عيسى; الحاج، مبطوش (جامعة محمد خيضر بسكرة - كلية الحقوق والعلوم السياسية - مخبر أثر الاجتهاد القضائي على حركة التشريع, 2020)
تعتبر الهجرة في مفهومها العام آلية من الآليات التي تساهم في حركة السكان عبر العالم، وأخذت صورا متعددة بين الأطر القانونية والمفاهيم السياسية، كنتاج عن الظروف الاقتصادية والاجتماعية التي تعرفها المجتمعات، والتي تدفع بالأفراد إلى الانتقال من مكان إلى آخر داخل وخارج حدود الدولة بحثا عن تحسين المستوى المعيشي، وهو ما شكل في مفهوم القواعد الناظمة لترتيبات ظروف معيشة الأفراد وتسوية وضعياتهم القانونية والاجتماعية، ومن بين الفئات التي اهتمت بها نصوص القانون الدولي ومنظمة العمل الدولية تحديدا فئة العمال المهاجرين وأفراد أسرهم، إذ تسهم المنظمة على تكريس الحقوق وتوفير الحماية لهذه الفئة من خلال أجهزتها وما يمنحه دستورها من صلاحيات في تطبيق الاتفاقيات المصدق عليها من قبل الدول المستقبلة لليد العاملة المهاجرة.
In its general concept, migration is one of the mechanisms that contribute to the movement of people around the world. It has taken multiple forms between legal frameworks and political concepts, as a result of the economic and social conditions defined by societies, which lead individuals to move from one place to another inside and outside borders of The State, in search of improving the standard of living, which was formed in the concept of rules governing the arrangements for the living conditions of individuals and the settlement of their legal and social status, among the groups concerned by the provisions of international law and the International Labor Organization in particular the category of migrant workers and members of their families. A system to entrench rights and provide protection to this category through its organs and the powers granted by its Constitution to implement the conventions ratified by the receiving countries of the labor force.
Keywords: المنظمات الدولية -- العمال المهاجرون -- حقوق الإنسان -- القانون الدولي -- القوانين والتشريعات